Diaphragmotomy to aid exposure during hepatobiliary surgery: a multi‐centre retrospective review of 31 dogs. (20th February 2020) - Dean, B.; Anderson, T.; Garcia‐Pertierra, S.; Jenkins, G.; Cantatore, M.; Craig, A.; Harris, K.; Ryan, T.
Abstract : Objectives: To report surgical technique, intra‐ and post‐operative complications, and short‐ and long‐term outcome following canine hepatobiliary surgery in which exposure of intra‐abdominal hepatobiliary lesions was aided by diaphragmotomy. Materials and Methods: Clinical records from four multi‐disciplinary UK‐based small animal referral hospitals were retrospectively reviewed for dogs in which diaphragmotomy was performed between January 2014 and May 2019. Signalment, diagnosis, surgery performed, diaphragmotomy technique, management of diaphragmotomy and pneumothorax, intra‐ and post‐operative complications, short‐term outcome and long‐term outcome were recorded. Results: Thirty‐one cases were identified. The most common hepatobiliary surgeries performed alongside diaphragmotomy were single hepatic lobectomy (14/31) and cholecystectomy (11/31). The most common diagnoses were hepatocellular carcinoma (10/31), gall bladder mucocoele (7/31) and hepatic nodular hyperplasia (4/31). Peri‐operative mortality rate was 9.7% (3/31 cases) though none of these deaths were considered attributable to diaphragmotomy. Post‐operative complications were encountered in 67.9% (19/28) cases that survived the peri‐operative period, of which 25.0% (7/28) suffered complications that were considered attributable or likely attributable to diaphragmotomy. These seven complications resolved following non‐surgical intervention. Follow‐up was available for 26 of 28 patients that survived to discharge at a median of 4‐months (range 10 days to 24 months) following surgery and revealed no evidence of complications related to diaphragmotomy. Clinical Significance: Diaphragmotomy appears safe and increases abdominal exposure of hepatobiliary lesions. The benefit of improved exposure must be carefully weighed up against the risks inherent in inducing pneumothorax.